KEBIJAKAN KRIMINAL TERHADAP TINDAKAN ABORSI - Dwight Nusawakan (STIKES Pasapua Ambon, 2019)
Introduction : In the Indonesian legal system, abortion is prohibited because abortion is categorized as a criminal act or acts contrary to morality (unless the abortion is done for medical reasons) so that the perpetrator and/or person assisting in doing so may be subject to punishment which has been regulated in law as well as the of criminal law. Currently abortion is one of the most serious problems seen from the high rate of abortion that increases every year. In Indonesia, the frequency of abortion each year reaches 3 million murders. This is very worrying because the pregnancy rate in Indonesia is very high. Therefore required a set of rules that can cope with this abortion problem so that the problem of the culprit get a deterrent effect. Policy formulation rules relating to abortion will enable the eradication of abortion actions and it is expected that law enforcement officers can apply these rules well.